Dividends as a Signal or Merely a Routine? The Mediating Role of Dividend Policy on Firm Value - Dika Setia Nugraha; Hersugondo Hersugondo (InFestasi, 2026)
The primary objective of this study is to investigate whether dividend policy functions as a market signal or simply follows a standard corporate protocol. Furthermore, the research explores the capacity of dividend policy to bridge the relationship between corporate attributes and market value. By examining non-financial firms within the LQ45 index from 2020 to 2023, the study analyzes the impact of firm size, profitability, and cash holdings on corporate valuation, with dividend policy serving as an intervening factor. Utilizing a quantitative framework, the study employed panel data regression and the Sobel test to evaluate mediation outcomes. Following outlier removal, a final dataset of 26 observations was gathered via purposive sampling. The empirical findings suggest that while profitability significantly influences both firm value and dividend policy, variables such as firm size and cash reserves do not demonstrate a meaningful impact. Ultimately, the results indicate that dividend policy is not a significant mediator between company characteristics and overall firm value.